Necrotizing fasciitis after Caesarean section. Can this complication be avoided? - Raba, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Necrotizing fasciitis (NF) is a type of acute infection of the subcutaneous connective tissue, which spreads along the fasciae surrounding the muscles. It leads to the toxic shock syndrome and a high mortality rate. Survivors often suffer from complications, of which the most common include other hospital-acquired infections (76%), respiratory failure syndromes (29%) and acute renal failure (32%). The most common etiological agent of NF is Streptococcus pyogenes, alone or in combination with other pathogens. To reduce the risk of infections caused by Streptococci, most gynaecological and obstetric institutions recommend that pregnant women take bacteriological cultures prophylactically in the prenatal period and that prophylactic prenatal antibiotic therapy be administered to carriers. However this does not enable the risk of the disease to be eliminated completely. At present, when antibiotics are widely overused in various branches of medicine, there is an increase in the number of Streptococci strains expressing the M1 protein. A rise can also be observed in the percentage of Caesarean deliveries. This raises concerns about an increase in the frequency of NF following Caesarean sections. The main factor improving the prognosis for NF following a Caesarean section is an early surgical intervention. Knowledge of the clinical course of NF can be expected to increase the accuracy of diagnosis and speed of the introduction of aggressive surgical treatment and intensive antibiotic therapy, thus significantly reducing the mortality rate associated with the disease.